Left atrial volume in elite athletes: A meta-analysis of echocardiographic studies - Cuspidi, C.; Sala, C.; Tadic, M.; Baccanelli, G.; Gherbesi, E.; Grassi, G.; Mancia, G. (Scandinavian Journal of Medicine & Science in Sports, 2019)
Aim: Information on left atrium (LA) enlargement, as assessed by LA volume (LAV) instead of LA diameter, in the athletic population is scanty. To expand current knowledge on this issue, we performed an updated meta-analysis of echocardiographic studies. Design: The Ovid MEDLINE, PubMed, and Cochrane CENTRAL databases were searched for English language articles without time restriction up to February 2018 through focused, high sensitive search strategies. Studies were identified by crossing the following search terms: "athletes," "physical training," "left atrial size," "left atrial volume," "atrial function," and "echocardiography.". Results: Overall, 3145 subjects (2425 elite athletes and 720 active but not trained healthy controls) were included in 16 studies. Average LAV indexed to BSA (LAVI) was 37% higher in athletes as compared to nonathletic controls (31.0 ± 1.4 mL/m2 vs 22.2 ± 0.9 mL/m2), the standard means difference (SMD) being 1.12 ± 0.13 (CI: 0.86-1.89, P < 0.0001). SMD was higher in high-dynamic/high-static trained athletes (1.78 ± 0.24, CI: 1.30-2.20, P < 0.001) than in high-dynamic/low-static trained athletes 1.00 ± 0.16, CI: 0.70-1.30, P < 0.001). The statistical difference did not change after correction for publication bias and was not affected by a single study effect. Conclusions: Our meta-analysis suggests that the adaptation of LA to intensive physical training in elite athletes is characterized by a marked increase in LAVI; LA dilation is more pronounced in the subgroup of high-dynamic/high-static trained athletes. The functional and clinical implications related to advanced LA dilation in athletes and particularly in those engaged in high-dynamic/high-static disciplines deserve further investigations.